PRAKTIK SEWA MENYEWA SAWAH DALAM PERSPEKTIF EKONOMI ISLAM (STUDI DI DESA KUALA KERITANG, KECAMATAN KERITANG, KABUPATEN INDRAGIRI HILIR, PROVINSI RIAU) - Siti Muhana; Hansen Rusliani; Muhamad Subhan (CV. Aksara Global Akademia, 2024)
Leasing is one of the muamalah practices carried out by humans in everyday life. In Islam itself, it is highly recommended for humans to help each other, cooperate, because in reality humans cannot live well without the help of other humans. Rentals are also carried out by the people of Kuala Keritang village to fulfill their living needs. This type of research is a research method using qualitative research which is based on the research process by producing descriptive data in the form of writing and expressions obtained directly in the field. Data collection techniques use observation, interviews and documentation methods. To obtain valid data, researchers used primary data sources and secondary data. The results of this research are that the god-rental agreement in Kuala Keritang Village was carried out verbally, there was no written or other evidence that it was made directly between the rice field owner and the rice field tenant. The rental agreement is carried out when the rice field owner and tenant know each other and there are still family ties. Leasing is done because the tenants do not have land to manage and the rice field owners are no longer able to work on their own fields.